Efektivitas Kebijakan Hukum dalam Penanganan Kasus Bullying di Perguruan Tinggi dan Faktor Penghambat Implementasinya - Sylvia, Rena (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
This study aims to analyze the effectiveness of legal policies in addressing bullying cases in higher education institutions and to identify the key obstacles hindering their implementation. Despite the existence of various legal frameworks—such as Law Number 12 of 2012 on Higher Education, Law Number 35 of 2014 on Child Protection, Law Number 39 of 1999 on Human Rights, Ministry of Education Regulation Number 82 of 2015, and provisions in the Indonesian Criminal Code (KUHP)—bullying continues to occur and often goes unaddressed effectively. This research employs a normative juridical approach supported by empirical findings and recent academic literature. The results reveal that low awareness of human rights, inadequate reporting and protection systems, as well as the persistence of seniority culture, peer pressure, and social labeling, are major barriers to policy enforcement. Conversely, character education, the promotion of diversity, and victim-centered campus policies serve as complementary strategies that enhance legal effectiveness. The study emphasizes the need for an integrative approach that combines formal regulation with non-legal initiatives to build a safe, inclusive, and bullying-free academic environment.